2016 38th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2016
DOI: 10.1109/embc.2016.7591336
|View full text |Cite
|
Sign up to set email alerts
|

Random forests for dura mater microvasculature segmentation using epifluorescence images

Abstract: Automatic segmentation of microvascular structures is a critical step in quantitatively characterizing vessel remodeling and other physiological changes in the dura mater or other tissues. We developed a supervised random forest (RF) classifier for segmenting thin vessel structures using multiscale features based on Hessian, oriented second derivatives, Laplacian of Gaussian and line features. The latter multiscale line detector feature helps in detecting and connecting faint vessel structures that would other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…To analyze vascular integrity, a perfused dura mater model was observed using high-resolution digital epifluorescence, laser scanning confocal microscopy and computer-assisted morphometric analysis ( 31 ). The results of the advanced microscopic analysis revealed that large areas of the connective tissue stroma, thought previously to be avascular, possessed extensive microvascular networks ( 32 37 ). Further, the cessation of the ovarian hormone production following bilateral ovariectomy in Yucatan miniature pigs caused gradual (within 2 months) yet significant remodeling of these microvascular networks.…”
Section: Estrogen “Withdrawal” Initiates Vascular Remodeling and Duramentioning
confidence: 99%
“…To analyze vascular integrity, a perfused dura mater model was observed using high-resolution digital epifluorescence, laser scanning confocal microscopy and computer-assisted morphometric analysis ( 31 ). The results of the advanced microscopic analysis revealed that large areas of the connective tissue stroma, thought previously to be avascular, possessed extensive microvascular networks ( 32 37 ). Further, the cessation of the ovarian hormone production following bilateral ovariectomy in Yucatan miniature pigs caused gradual (within 2 months) yet significant remodeling of these microvascular networks.…”
Section: Estrogen “Withdrawal” Initiates Vascular Remodeling and Duramentioning
confidence: 99%
“…We use random forest (RF) classifier [8] based approach which is adapted for vessel structure and cell segmentation with high precision and recall [7], [9]. Our feature bank is optimized to capture curvilinear structures of varying width as well robust to scale changes.…”
Section: Optimized Feature Bank For Random Forest Classifier Basedmentioning
confidence: 99%
“…They are based on Hessian eigenvalues based multiscale Frobenius norms, multiscale Laplacian of Gaussians (LoG), a multiscale line detector [2]. Here we provide the basic details of each of these features and refer to [7] more details of these optimized feature bank for vessel segmentation.…”
Section: Optimized Feature Bank For Random Forest Classifier Basedmentioning
confidence: 99%
See 2 more Smart Citations